Fine Needle Aspiration of Thyroid Nodules Using the Bethesda System for Reporting Thyroid Cytopathology: An Institutional Experience in a Rural Setting - Aili Guo; Yuuki Kaminoh; Terra Forward; Frank L. Schwartz; Scott Jenkinson (International Journal of Endocrinology)
Background. Fine needle aspiration (FNA) remains the first-line diagnostic in management of thyroid nodules and reduces unnecessary surgeries. However, it is still challenging since cytological results are not always straightforward. This study aimed to examine the results of thyroid FNA using the Bethesda system for reporting thyroid cytopathology (TBSRTC) to establish the level of accuracy of FNA procedures in a rural practice setting. Method. A retrospective chart review was conducted on existing thyroid FNA performed in a referral endocrine center between December 2011 and November 2015. Results. A total of 159 patients (18–88 years old) and 236 nodule aspirations were performed and submitted for evaluation. 79% were benign, 3% atypia/follicular lesion of unknown significance (AUS/FLUS), 5% follicular neoplasm/suspicious for follicular neoplasm (FN/SFN), 4% suspicious for malignancy (one case was indeed an atypical parathyroid neoplasm by surgical pathology), 2% malignant, and 7% nondiagnostic. Two cases also had advanced molecular analysis on FNA specimens before thyroidectomy. Conclusion. The diagnostic yield of FNA cytology from our practice in a rural setting suggests that accuracy and specificity are comparable to results from larger centers.